Synthesis of the modified SBA-15 mesoporous silica with TAN ligand to preconcentrate and determine trace amounts of Ni (II) ions in water and wastewater samples - Amouzad Mahdirajeh, Taha; Mirabi, Ali; Habibi Juybari, Mohammad; Zafar Mehrabian, Ramin; Jalilian, Hamid Reza (Frontiers in Chemistry, 2024)
The synthesis of modified mesoporous silica (SBA-15), a powerful and highly effective adsorbent, was provided for the preconcentration, extraction, separation, and determination of trace amounts of Ni (II) ions. In this method, SBA-15 modified with 1-(2-Thiazolylazo)-2naphthol (TAN) was used as a suitable absorbent. The absorption of Ni (II) ions was studied using FAAS technique. TEM, TGA, BET, EDS, FT-IR, and CHNS elemental analysis techniques were used to assess the characteristics of SBA-15 and TAN/SBA-15. Effective parameters (pH, amount of nanocomposite, extraction time, and type of recovery solvent) for extracting Ni (II) ions via TAN/SBA-15 were investigated. The merit figures of the method were obtained with appropriate results, such as detection limit, accuracy, enrichment factor, and preconcentration factor. The calibration curve was linear within the range of 5.0-50 ng mL -1 with a detection limit of 1.8 ng mL -1 . High preconcentration, small relative standard deviations, and enrichment factors (about 100) were represented by the statistical analysis. The proposed method for measuring Ni (II) ions was used at trace levels in real samples such as sea water, river water, well water, wastewater from textile factory, wastewater from an electrical power station, wastewater from an MDF factory and wastewater from a food industrial company with satisfactory results.